Electrochemical Oxidation of Methanol on Pt-SnOx/C Catalysts Characterized by Electrochemistry Methods. Issue 14 (1st January 2015) - Sun, Xigui; Gao, Kewei; Pang, Xiaolu; Yang, Huisheng; Volinsky, Alex A.
Abstract : Pt-SnOx /C catalysts with Pt/Sn atomic ratio of 1:1, 2:1, 3:1, 4:1 and 5:1 were prepared by the impregnation method. The electrochemical process of methanol oxidation on these five catalysts was studied using cyclic voltammetry and electrochemical impedance spectroscopy two simple real-time methods. Impregnation is a stable way to prepare Pt-SnOx /C catalysts with accurate stoichiometry and uniform particle size, which increased from 3.8 nm to 5.4 nm as the Sn content decreased. The maximum current density of methanol electrochemical oxidation initially increased and then decreased with the Sn content, and Pt3 -SnOx /C exhibited the highest value of about 16.6 mA·cm −2 . Methanol electrochemical oxidation on the Pt-SnOx /C catalyst surface changed from adsorption to dehydrogenation, to hydrolysis and finally oxidation as the electrode potential increased from 0 V to 0.85 V. The main intermediate created during methanol electrochemical oxidation was COads . The existence of Sn atoms decreased the onset potential of the hydrolysis reaction, and consequently promoted methanol electrochemical oxidation. Interestingly enough, the highest reaction rate was obtained at about 0.65 V due to similar reaction rates of COads oxidation and methanol dehydrogenation.